DESCRIPTION OF THE LEVELS OF ASPARTATE AMINOTRANSPHERASE (AST) AND ALANINE AMINOTRANSPHERASE (ALT) ENZYME IN PATIENTS WITH CIRROSIS OF THE LIVER AT EPHARINA HOSPITAL ETAHAM BERASTAGI - Wahyuni Tarigan, Sri; Wooton, Ian; Maswan, Maswan; Lubis, Josep; Syafrina, Efrin (Universitas Efarina, 2021)
Cirrhosis of the liver is a condition in which the liver slowly deteriorates which continues over a long period of time (chronic). The cells and liver tissue that is damaged and then turned into scar tissue so that the function of the liver will progressively decrease. This research is an observational descriptive by using medical records of patients with liver cirrhosis at the Efarina Etaham Berastagi Hospital, in January-July 2019. The sample of the study is 25 samples. The results obtained by patients with liver cirrhosis highest proportion based on male sex (80%), based on age, age group 40-50 years (28%), 51-60 years (64%) Based on AST levels 21 respondents (84 % ), Based on ALT levels of 22 respondents (88%). Conclusions from the results of the study, the examination should be done several times to get accurate results